P140 BPIFB1/LPLUNC1 is a novel marker for the bronchiolised epithelium in IPF. (14th November 2013) - Bingle, CD; Araujo, B; Wallace, WA; Marriott, HM; Hirani, N; Bingle, L
Abstract : Idiopathic pulmonary fibrosis (IPF) is an irreversible and progressive lung disease with limited life expectancy after diagnosis. Histopathological studies of IPF lungs reveal the typical "Usual Interstitial Pneumonia" (UIP) pattern, with epithelial hyperplasia, areas of scarring with fibroblast foci and characteristic morphological abnormalities, including bronchiolization of alveolar ducts and honeycomb cysts. Although it seems likely that bronchiolar abnormalities are caused by changes in epithelial cell differentiation, specific markers of this process remain elusive. By analysis of published array data sets from IPF patients, we identified BPIFB1/LPLUNC1 as a potential candidate marker for the disease. Indeed, in the largest published study the gene was the most differentially expressed transcript. This putative innate defence protein is normally expressed in the airway submucosal glands and in a population of MUC5A/C positive goblet cells in the upper airways. Analysis of lung tissue from UIP revealed strong staining of BPIFB1/LPLUNC1 within the bronchiolized epithelium lining the honeycomb cysts as well as in the mucosubstance filling these regions. MUC5B was localized to the same cells as BPIFB1/LPLUNC1 wheras the related protein, BPIFA1/SPLUNC1, was not co-expressed. This pattern of staining was not seen in other chronic lung diseases, suggesting a degree of specificity for IPF. To shed light on a temporal association of expression of these markers with fibrosis development we studied mice exposed to the pro-fibrotic agent bleomycin (Bleo). MUC5B and LPLUNC1 were co-expressed in a population of goblet cells in the airways of mice within 3–7 days of Bleo exposure, prior to the onset of fibrosis. Continued expression was seen during the development of fibrosis between 14–21 days post treatment. In contrast, in mice treated with PBS neither protein was seen (due to mouse airways being essentially free of goblet cells). Staining was absent from the fibrotic regions and the lung parenchyma, as is the case in IPF. Our data show that the ectopic expression seen in human IPF, is mirrored by that seen in the fibrotic mouse model. Furthermore it suggests that BPIFB1/LPLUNC1 may be worthy of further study as potential marker for the disease.